2013
DOI: 10.4149/av_2013_04_462
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase inhibitors suppress coxsackievirus B3 growth in vitro and myocarditis induced in mice

Abstract: Summary. -Clinical importance of myocarditis, predominantly caused by coxsackievirus B3 (CVB3), is recently rising. However, a detailed mechanism of pathogenesis of CVB3 myocarditis still needs to be clarified. Recently, it has been reported that histone modifications including acetylation are involved in coxsackievirus replication. To examine whether the CVB3 replication requires histone acetylation, histone deacetylase (HDAC) inhibitors were employed. We found that the HDAC2 activity increased in virus-infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
(18 reference statements)
0
8
0
Order By: Relevance
“…Aside from SIRT1, we examined the effect of HDAC1—a member of the classic HDAC family, whose members are located in the nucleus—on p53 acetylation. Shim et al have found that inhibition of HDAC activity reduces CVB3 replication, and Zhou et al reported that inhibition of HDAC activity by hydroxamic acid or TSA reduces cardiomyocyte apoptosis. We can speculate that HDAC1 promotes the CVB3‐induced cardiomyocyte apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Aside from SIRT1, we examined the effect of HDAC1—a member of the classic HDAC family, whose members are located in the nucleus—on p53 acetylation. Shim et al have found that inhibition of HDAC activity reduces CVB3 replication, and Zhou et al reported that inhibition of HDAC activity by hydroxamic acid or TSA reduces cardiomyocyte apoptosis. We can speculate that HDAC1 promotes the CVB3‐induced cardiomyocyte apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, VPA may function through the HDAC inhibitory activity to attenuate inflammation in viral myocarditis. In addition, Shim et al reported that Histone deacetylase inhibitors Trichostatin A could suppress CVB3 replication in Hela cells in vitro, and subsequently reduces CVB3 titers in the heart and protects mice from myocarditis [ 17 ]. In our study, we also observed significantly decreased CVB3 replication in heart tissues in vivo, suggesting that decreased viral replication is also necessary for VPA-mediated amelioration of viral myocarditis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is reasonable to hypothesize that HDAC inhibitor plays a protective role in viral myocarditis. One study showed that HDAC inhibitors could suppress CVB3 growth in vitro and CVB3-induced myocardial injury in vivo [ 17 ]. However, the role and the detailed mechanism of VPA in viral myocarditis remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…This result is in conflict with the Shim et al study in which TSA suppressed the CVB3 replication at 24 h p.i. in HeLa cells and protected against CVB3-induced myocardial injury in vivo ( 37 ). The reason for this apparent discrepancy is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this apparent discrepancy is unclear. However, we used the CVB3 Nancy strain in the current study, whereas Shim et al used the Woodruff strain ( 37 ). The different CVB3 strain might account for the discrepancy.…”
Section: Discussionmentioning
confidence: 99%